2020
DOI: 10.1140/epjc/s10052-019-7601-y
|View full text |Cite
|
Sign up to set email alerts
|

Continuous phase transition and microstructure of charged AdS black hole with quintessence

Abstract: First, Maxwell equal-area law was used to discuss the conditions satisfied by the phase transition of charged AdS black holes with cloud of string and quintessence, and it was concluded that black holes have phase transition similar to that of vdW system. The phase transition depends on the electric potential of the black hole and is not the one between a large black hole and a small black hole. On the basis of this result, we study the relation between the latent heat of phase transition and the parameter of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 85 publications
(67 reference statements)
1
26
0
Order By: Relevance
“…The continuous phase transition point depends only on the position ratio of the two horizons, and is not a single function of the electric charge, mass, and cosmological constant of the black hole. When a continuous phase transition occurs, the electric potential at the black hole horizon is a constant, which is similar to AdS black holes [36,37]. The phenomenon reflects that when RN-dS spacetime evolves to pure dS spacetime, the evolution process of spacetime is different due to the different charges in spacetime.…”
Section: Conclusion and Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The continuous phase transition point depends only on the position ratio of the two horizons, and is not a single function of the electric charge, mass, and cosmological constant of the black hole. When a continuous phase transition occurs, the electric potential at the black hole horizon is a constant, which is similar to AdS black holes [36,37]. The phenomenon reflects that when RN-dS spacetime evolves to pure dS spacetime, the evolution process of spacetime is different due to the different charges in spacetime.…”
Section: Conclusion and Discussionmentioning
confidence: 91%
“…The thermodynamic properties of AdS black holes have been studied extensively . The study of the thermodynamic properties of black holes will not only deepen understanding of the nature of black holes, but also help to understand the microscopic particles inside black holes [30][31][32][33][34][35][36][37][38]. People first found that the charged AdS black hole has a characteristic similar to the Van de Waals phase transition when the independent variable P − V was selected.…”
Section: Introductionmentioning
confidence: 99%
“…In this section, we first introduce the thermodynamics charged AdS black hole surrounded by quintessence by reviewing Refs. [46][47][48][49]. The line element of such a black hole is expressed as…”
Section: IImentioning
confidence: 99%
“…Further, the effect of dark energy on the efficiency of black hole heat engines has been studied in [33] showing that quintessence can improve the efficiency, especially at the critical point. Maxwell's equal area law was used by Guo in [34] to show that phase transitions of AdS black holes with quintessence can still be mapped to those of the liquid-gas system. More recently, it has been shown that quintessence alters the high temperature phase structure of black holes undergoing the Hawking-Page transition [35].…”
Section: Introductionmentioning
confidence: 99%